A DIGITAL NURSING CARE DELIVERY MODEL TO IMPROVE QUALITY OF LIFEIN HEART FAILURE: A SCOPING REVIEW - Eza Kemal Firdaus; Letícia Carvalho Mendes; Eoin Patrick Byrne; Vijay Kumar (Program Studi Ilmu Keperawatan Universitas Jember, 2025)
Background: Conventional treatment reduces symptoms, hospitalizations but remains insufficient in enhancing long-term QoL. Telerehabilitation has emerged as a promising digital nursing care approach to address these limitations. Objective: Aimed to examine effectiveness of telerehabilitation in improving QoL for HF patients. Methods: Search was conducted in PubMed, SAGE , Wiley Online Library, ProQuest, ScienceDirect for randomized controlled trials published between 2012 and 2022. PRISMA framework guided study selection, while PICO model defined eligibility criteria. Methodological quality was assessed using the JBI appraisal tool. Results: 3,724 articles screened, 5 randomized controlled trials met inclusion criteria. Interventions included mobile phone-based telemonitoring, structured telephone support, home-based applications, nurse-led collaborative programs. All studies reported improvements in QoL, self-care behaviors, health outcomes, alongside reductions in hospital readmissions. JBI scores rangied from 11/ 13 to 13/13, indicating strong methodological rigor. Conclusion: Telerehabilitation effectively enhances QoL in HF patients by strengthening self-management, enabling continuous monitoring, supporting psychosocial well-being. Despite challenges related to accessibility, sustainability, resource allocation, telerehabilitation offers a feasible, evidence-based strategy to improve QoL in HF management.